Financing renewable energy generation in SSA: Does financial integration matter? - Hervé Kaffo Fotio; Tii Njivukuh Nchofoung; Simplice Asongu (African Governance and Development Institute (AGDI), 2022)
Despite growing attention on the role of renewable energy in promoting economic growth and environmental sustainability, its adoption rate remains uncomfortably low, especially in developing countries. This study attempts to explore the ways to extend the installed capacity of renewable energy in 16 sub-Saharan African (SSA) countries over the period 1980-2017. The results from panel cointegration econometric techniques suggest that policies to enhance financial integration should increase the installed capacity of renewable energy in SSA, though the beneficial effect is only statistically significant in the long run. This effect holds, although disproportionately when the financial integration index is disaggregated into its de facto and de jure aspects. Moreover, the quantile regression analysis reveals that the effect of financial integration on renewable energy capacity is positive but heterogeneous across the conditional distribution of renewable energy capacity. However, the positive effect of financial integration is not enough to ensure the diversification of the energy mix, measured as the share of renewable installed capacity in the total installed capacity. The results show that economic growth is positively linked to renewable energy generation capacity while financial development is negatively associated with renewable energy production. Overall, these findings suggest that policies to increase the openness to foreign capitals are welcomed as far as renewable energy generation is concerned.
Keywords: 330; Financial integration; Renewable energy; Sub-Saharan Africa; Cointegration